IMPLEMENTASI TEKNIK RELAKSASI NAFAS DALAM UNTUK MENGATASI NYERI KEPALA PADA PASIEN HIPERTENSI PADA NY S DI DESA SENON PURBALINGGA - Wahyuma Agung Kurniawan; Wiwik Priyatin; Yolinda Suciliyana (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
Hypertension is also known as high blood pressure. Hypertension can cause a number of symptoms such as epistaxis, palpitations, shortness of breath, and headaches after a day's activities if the systolic and diastolic pressures remain above 140 and 90 mmHg respectively. Deep breathing relaxation technique is an independent nursing intervention where the nurse teaches the patient how to take deep breaths, slow breaths (maximum holding inspiration) and how to exhale slowly to relax muscle tension that supports pain. Purpose of this research is to find out how to implement deep breathing relaxation techniques to reduce headaches in hypertensive patients in Mrs. S, Senon Village in Purbalingga. The results of the nursing implementation stated that deep breathing relaxation techniques can reduce headaches in hypertensive patients. after implementing the deep breathing relaxation technique for 3 days on Mrs. S with hypertension. This is evidenced by measuring the pain scale on the first day with a scale of 5 (moderate), then on the second day with a pain scale of 5 (moderate) to 4 (moderate), and on the third day with a pain scale of 4 (moderate) to 3 (mild). The application of Deep Breathing Relaxation is very effective in reducing the intensity of headaches experienced by Hypertension patients.